SMART CITY GOVERNANCE IN THE NEW INDONESIAN CAPITAL (IKN) OF NUSANTARA; A FRAMEWORK FOR INTEGRATING TECHNOLOGY AND CITIZEN PARTICIPATION - Rachmawati Novaria; Faisal Razak; Nurul Huda (Yayasan Adra Karima Hubbi, 2025)
Background: The establishment of Nusantara (IKN) as Indonesia’s new capital represents a monumental endeavor in urban development, explicitly aiming to be a “smart city.” However, the global challenge for smart cities lies not merely in deploying technology, but in creating governance structures that effectively integrate these digital systems with inclusive, genuine citizen participation. This research addresses the critical gap in how IKN’s smart city ambitions will be governed, focusing on the essential synergy between technological infrastructure and participatory democracy. Purpose: This study aims to develop and propose a comprehensive governance framework specifically tailored for IKN Nusantara. The objective is to conceptualize a model that operationalizes the integration of advanced technologies (e.g., IoT, AI, big data) with robust mechanisms for citizen engagement in policy-making and urban management. Methods: A qualitative, constructive research design was employed. The framework was developed through a rigorous analysis of existing global smart city governance models, a systematic review of IKN’s foundational policy documents, and in-depth, semi-structured interviews with key stakeholders, including urban planners, technology experts, and civil society representatives. Results: The primary outcome is the “IKN Integrated Governance Framework” (IGF). This framework identifies four critical pillars: (1) A unified data and technology platform, (2) Multi-channel citizen participation portals (digital and physical), (3) Data-driven, transparent decision-making processes, and (4) Adaptive regulatory oversight. The findings emphasize that a technology-first approach without embedded participation mechanisms risks creating an exclusionary, top-down city. Conclusion: The proposed framework provides an essential blueprint for IKN to avoid the pitfalls of “techno-solutionism.” By structurally embedding citizen participation within the technological architecture, Nusantara can pioneer a smart city governance model that is not only efficient and intelligent but also human-centric, resilient, and democratically accountable.